2021
DOI: 10.1111/ctr.14279
|View full text |Cite
|
Sign up to set email alerts
|

Transplant outcomes using kidneys from high KDPI acute kidney injury donors

Abstract: Kidney transplant (KT) outcomes from high kidney donor profile index (KDPI ≥85%) donors with acute kidney injury (AKI) remain underreported. KT from 172 high KDPI Acute Kidney Injury Network (AKIN) stage 0‐1 donors and 76 high KDPI AKIN stage 2‐3 donors from a single center were retrospectively assessed. The AKIN 2‐3 cohort had more delayed graft function (71% vs. 37%, p < .001). At one year, there were no differences in the estimated glomerular filtration rate (44 ± 17 vs. 46 ± 18, p = .42) or fibrosis on pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(61 citation statements)
references
References 17 publications
(47 reference statements)
1
60
0
Order By: Relevance
“…Previously, we reported that severe AKI donors with high KDPI (surrogate for age) are at higher risk for PNF. 16 In high KDPI the overall incidence of PNF was higher in the AKIN 2-3 group compared to AKIN 0-1 (5.3% vs. 0.6%, p = .02). 16 PNF in the study was related to high KDPI and chronic changes that were missed on preimplantation biopsy.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Previously, we reported that severe AKI donors with high KDPI (surrogate for age) are at higher risk for PNF. 16 In high KDPI the overall incidence of PNF was higher in the AKIN 2-3 group compared to AKIN 0-1 (5.3% vs. 0.6%, p = .02). 16 PNF in the study was related to high KDPI and chronic changes that were missed on preimplantation biopsy.…”
Section: Discussionmentioning
confidence: 79%
“…PNF rates here are similar to what we have previously reported 4 and were related to high KDPI kidney. Previously, we reported that severe AKI donors with high KDPI (surrogate for age) are at higher risk for PNF 16 . In high KDPI the overall incidence of PNF was higher in the AKIN 2–3 group compared to AKIN 0–1 (5.3% vs. 0.6%, p = .02) 16 .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Despite these limitations, we feel that our experience with DGF and outcomes are valuable. Despite using donors with higher risk features and overall higher rates of DGF, we have reported excellent outcomes [ 8 , 9 , 16 , 19 , 20 ]. Moreover, this current study provides granular details specific to DGF that are not available from larger database studies.…”
Section: Discussionmentioning
confidence: 99%